Study on the rate of using, awareness and satisfaction of scientific database by Mazandaran University of Medical Science student’s and related factors to it - Mousavi Chalak, Afshin; Riahi, Aref (Researcher Bulletin of Medical Sciences, 2020)
Introduction: Scientific databases are one of the most important information resources in academic community and can play determinative role in different aims and goals of student. This study aimed to determine the rate of using, awareness and satisfaction of scientific database among student of Mazandaran University of Medical Sciences. Materials and Methods: This study is an applied-survey study and has been done during the 2016-2017 educational period. Self-questionnaire that made according to review of internal and external resources about the subject (in 6-sections), and its reliability and validity being approved, distributed among 238 Students of Mazandaran University of Medical Sciences (Master, PhD, Doctors and Medical residents). To analysis data, we use descriptive statistics, statistical test and SPSS 16. Results: Findings show that most of student use scientific database because of clinical activities (average of 4.27). Also we funded that most knowledge level of those students about database were ISI (average of 4.43) and they used Pubmed more than other database (4.30). Also the highest satisfaction rate of database was ISI (4.28) and “unfamiliarity with the English language "funded as the most barriers related to use of scientific database. Conclusion: Rate of using, awareness and satisfaction of scientific database among student of Mazandaran University of Medical Sciences was more than average and close to high level. Mazandaran Medical Science University by planning and tacking suitable policy and also destroy of barriers and challenges can provided better conditions of student’s using scientific database and created cause of growth of their scientific and professional developments.